2001
DOI: 10.1097/00003246-200112000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Delayed emergency department presentation in critically ill patients

Abstract: Because of poor understanding of the gravity and natural progression of their symptoms, most critically ill patients waited >24 hrs to present to our emergency department. Education on warning symptom recognition for serious illnesses may be warranted not only for patients themselves but also for family members and caregivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Among patients who were critically ill and traumatically injured, the uninsured were also less likely than those with insurance to be admitted to a hospital (adjusted OR 0.63; 95% CI, 0.62-0.65) (42). Although there were no significant differences in the time it took patients to arrive at the emergency department (38), in one study, patients who were uninsured and critically ill were less likely to use an ambulance to get to the hospital than those who had insurance (OR, 0.47; 95% CI, 0.23-0.98) (21). In a second study that was better able to adjust for potential confounding by demographics and severity of illness at presentation, differences were not significant (OR, 0.85 95% CI, 0.53-1.36) ( leave the hospital (OR, 4.51; 95% CI, 1.46-13.93) (25).…”
Section: The Association Between Insurance and Care For Patients Who mentioning
confidence: 94%
“…Among patients who were critically ill and traumatically injured, the uninsured were also less likely than those with insurance to be admitted to a hospital (adjusted OR 0.63; 95% CI, 0.62-0.65) (42). Although there were no significant differences in the time it took patients to arrive at the emergency department (38), in one study, patients who were uninsured and critically ill were less likely to use an ambulance to get to the hospital than those who had insurance (OR, 0.47; 95% CI, 0.23-0.98) (21). In a second study that was better able to adjust for potential confounding by demographics and severity of illness at presentation, differences were not significant (OR, 0.85 95% CI, 0.53-1.36) ( leave the hospital (OR, 4.51; 95% CI, 1.46-13.93) (25).…”
Section: The Association Between Insurance and Care For Patients Who mentioning
confidence: 94%
“…Timely access to care is particularly important to optimize outcomes for acute conditions in need of rapid definitive treatment such at stroke and myocardial infarction [58,59]. Given the need for early and aggressive treatment of NSTI, it is not surprising that our study patients with government-supported insurance or those without any insurance were less likely to survive the index hospitalization compared to privately insured patients.…”
mentioning
confidence: 89%
“…A number of previous studies on conditions ranging from peripheral vascular disease to colon cancer have demonstrated that uninsured or under-insured patients present later and with more advanced disease than patients with private insurance resulting in disparities in disease outcomes [58][59][60][61][62][63][64][65]. Timely access to care is particularly important to optimize outcomes for acute conditions in need of rapid definitive treatment such at stroke and myocardial infarction [58,59].…”
mentioning
confidence: 99%
“…21 However, the majority of ACS studies report the opposite, with substantial, significant delays attributable to HCP contact. 6,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] In general, studies of care-seeking delay, although plentiful, have not consistently measured HCP contribution to delay primarily because most studies use either retrospective patient chart review 36 or EMS logs to document the interval of time from acute symptom onset (ASO) to ED arrival. As a consequence, we do not accurately know how much time can be attributed to provider delay in contrast with patient and lay other delay.…”
Section: Introductionmentioning
confidence: 99%
“…A timeconsuming behavioral response is consultation with an HCP, yet we know little about how HCPs come to their consistently time-consuming decisions. If it is consistently shown that calling an HCP impedes the ACS care-seeking process, 6,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] and if we can reduce the "Door-to-Needle" time in the treatment of ACS in the ED, 64 there is an even more compelling need to study the decision-making processes used by HCPs, primarily physicians and their office personnel, when called by individuals reporting ACS symptoms. On the basis of the present study and prior research, 6,22-35 and until we develop an ACS management protocol based on the incidence of calls to HCP offices, patients with ACS should be advised to avoid calling an HCP and to go directly to the ED to ensure rapid access to highly time-dependent reperfusion therapies.…”
mentioning
confidence: 99%